Motivation, Image and Potentials of tourist attractions affecting satisfaction in military tourist attraction: Baan Pongnak, Surasak montri Barrack, Lampang province - Homkanchan, Nanta; Sirisugandha, Thanakorn (Journal of Thammawat, 2024)
This research has the objectives to study 1) levels of opinions in motivation, images and tourist attraction potentials affecting satisfaction in military tourist attraction: Baan Pongnak, Surasak montri Barrack, Lampang province and 2) Analysis of opinions on motivation, image and potential of tourist attraction affecting satisfaction in military tourist attraction: Baan Pongnak, Surasak montri Barrack, Lampang province. The sample group was the Thai tourists who had visited military tourist attractions at Baan Pongnak, Surasak montri Barrack, Lampang province totaled 385 persons. This is survey research, The tools used was a questionnaire and used descriptive statistics of percentage, means and standard deviations and inferential statistics of Enter Multiple Regression Analysis. The research findings were 1) levels of opinion of image affected satisfaction in military tourist attraction: Baan Pongnak, Surasak montri Barrack, Lampang province at the highest level followed by motivation at the highest level and potential of the tourist attraction also at the highest level respectively and 2) the results of Enter Multiple Regression Analysis found that image and potentials of tourist attraction affected satisfaction in the military tourist attraction: Baan Pongnak, Surasak montri Barrack, Lampang province at the statistical significance level of .01 while motivation did not affect satisfaction in military tourist attraction: Baan Pongnak, Surasak montri Barrack, Lampang province at the statistical significance level of .05.